Performance Analysis of Single Cylinder Diesel Engine on Biodiesel Fuel Temperature Variation - Erwin Pratama; Abrar Riza; Steven Darmawan (Fakultas Teknik Universitas Pancasila, 2026)
The use of biodiesel or bio solar fuel continues to grow in line with the increasing awareness of renewable energy and environmental concerns. However, the relatively high viscosity of bio solar fuel can affect the performance of diesel engines. This study aims to analyze the effects of fuel temperature variation using a heater on the performance of diesel engines. The research method employed was experimental testing on a single cylinder Jiangdong 170F diesel engine with fuel heating set at temperatures 40oC, 50oC, 60oC, and 70oC. The parameters analyzed include power, torque, fuel flow rate, thermal efficiency, and Brake Specific Fuel Consumption. The test results show that at a temperature of 50oC, the engine produced the highest power and torque at a rotational speed of 2600 rpm with a torque of 6.2 Nm and power output of 1.68 kW. At temperatures of 70oC the highest thermal efficiency was observed along with reductions in fuel consumption and BSFC at the same engine speed, yielding a thermal efficiency of 34.04%, a fuel consumption rate of 1.128×10-5 kg/s and a BSFC of 6.912×10-5 g/kWh. These results suggest that a temperature of 50oC is recommended for achieving high power and torque at high speeds, while temperature 70oC is recommended for attaining high thermal efficiency and lower fuel consumption at high engine speeds.